2020
DOI: 10.3389/fchem.2020.00297
|View full text |Cite
|
Sign up to set email alerts
|

MXenes and Their Applications in Wearable Sensors

Abstract: MXenes, a kind of two-dimensional material of early transition metal carbides and carbonitrides, have emerged as a unique class of layered-structured metallic materials with attractive features, as good conductivity comparable to metals, enhanced ionic conductivity, hydrophilic property derived from their hydroxyl or oxygen-terminated surfaces, and mechanical flexibility. With tunable etching methods, the morphology of MXenes can be effectively controlled to form nanoparticles, single layer, or multi-layer nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
125
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(130 citation statements)
references
References 98 publications
(84 reference statements)
0
125
0
Order By: Relevance
“…Moreover, such heterostructures can be very suitable for use in wearable health care devices such as sweat based glucose/electrolyte sensors, pulse sensors, etc., for early medical diagnosis. [ 252 ] MXenes also exhibit considerable magnetization effects, even at room temperature. [ 253 ] Therefore, strong magnetic manipulation can be expected in these heterostructures, which can lead to design appealing 2D spintronic devices.…”
Section: Future Technological Scopes With Mxene/organic 2d Heterostrumentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, such heterostructures can be very suitable for use in wearable health care devices such as sweat based glucose/electrolyte sensors, pulse sensors, etc., for early medical diagnosis. [ 252 ] MXenes also exhibit considerable magnetization effects, even at room temperature. [ 253 ] Therefore, strong magnetic manipulation can be expected in these heterostructures, which can lead to design appealing 2D spintronic devices.…”
Section: Future Technological Scopes With Mxene/organic 2d Heterostrumentioning
confidence: 99%
“…2D MXenes or its composites show enhanced mechanical flexibility and stretchability, which has enabled its wide application in the fields of wearable sensors. [211,275] Toward the use of 2D organic materials for wearable sensors, 2D metal organic framework layer based nanodevices have been demonstrated for various functional sensory purposes. [276] In particular, the abundant accessible active sites available on such organic frames could play a vital role for sensing applications.…”
Section: Wearable Medical Sensormentioning
confidence: 99%
“…3 The high elastic mechanical strength 4 , electronic conductivity 5,6 , chemical stability [7][8][9] , and hydrophilicity 10,11 of MXenes have opened broad prospects for their applications in a variety of industrial and technological areas including energy storage, optoelectronics, spintronics, catalysis, and sensing. [12][13][14][15][16][17][18][19][20][21][22][23] Although there is significant research effort in the optical 24,25 and electronic 11,26,27 properties of MXenes, the magnetic properties of these materials for spintronic application is relatively unexplored. 28 The intrinsic properties of MXenes are mainly determined by the transition metal in the MAX phase.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ti 2 C MXene was theoretically and experimentally investigated for gas sensor applications. 22 Simulation studies confirmed that single-layer Ti 2 C shows higher sensibility for NH 3 than for CO 2 , O 2 , H 2 , and CH 4 when its surface is enriched with oxygen functional groups. In addition, fabricated flexible Ti 2 C/polyimide sensors showed excellent NH 3 detection.…”
Section: Applicationsmentioning
confidence: 68%
“…The grafting of poly(2-(dimethylamino)ethyl methacrylate) on the V 2 C surface allowed for the fabrication of sensors that are sensitive to CO 2 and temperature. 22 …”
Section: Applicationsmentioning
confidence: 99%